2016
DOI: 10.4236/jtr.2016.44022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cytotoxic T-Cells on the Dynamics of Co-Infection of HIV-1 and <i>Mycobacterium tuberculosis</i>

Abstract: Enhancement of the Human Immunodeficiency Virus (HIV) specific cytotoxic Tcells mechanisms in an HIV-1 and Mycobacterium tuberculosis (Mtb) co-infected individual seems to improve the clinical picture of an individual by reducing Acquired Immuno Deficiency Syndrome (AIDS) state progression rate. In this paper, we develop a system of deterministic differential equations representing the immune cells involved in an HIV-1 and Mtb co-infected individual. Results show that although the non-lytic arm of the HIV-1 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The authors concluded, in line with the experimental studies outlined above, that coinfection completely alters the cytokine environment, macrophage decline is correlated to CD4+ T cell decline and increased viral loads, and that these mechanisms result in lower recruitment to the site of infection allowing the reactivation of TB (92) Kirschner 1999. Results showed that both the lytic and nonlytic factors of the HIV-specific CTLs are important in controlling HIV infection in coinfected individuals and the authors advocate for drugs and/or vaccines that enhance CTL mechanisms (97). Table 1 highlights the important features of each model and key results obtained from the simulations.…”
Section: Potential Impact and Use Of Computational Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded, in line with the experimental studies outlined above, that coinfection completely alters the cytokine environment, macrophage decline is correlated to CD4+ T cell decline and increased viral loads, and that these mechanisms result in lower recruitment to the site of infection allowing the reactivation of TB (92) Kirschner 1999. Results showed that both the lytic and nonlytic factors of the HIV-specific CTLs are important in controlling HIV infection in coinfected individuals and the authors advocate for drugs and/or vaccines that enhance CTL mechanisms (97). Table 1 highlights the important features of each model and key results obtained from the simulations.…”
Section: Potential Impact and Use Of Computational Modelingmentioning
confidence: 99%
“…Mufudza et al., 2016 incorporated HIV specific cytotoxic T cell mechanisms (not Mtb specific CTLs) into the model described by Kirschner 1999. Results showed that both the lytic and non-lytic factors of the HIV-specific CTLs are important in controlling HIV infection in coinfected individuals and the authors advocate for drugs and/or vaccines that enhance CTL mechanisms ( 97 ). Table 1 highlights the important features of each model and key results obtained from the simulations.…”
Section: Potential Impact and Use Of Computational Modelingmentioning
confidence: 99%